Biological versus mechanical aortic valve replacement in non-elderly patients: a single-centre analysis of clinical outcomes and quality of life - Stocco, Fabio; Fabozzo, Assunta; Bagozzi, Lorenzo; Cavalli, Chiara; Tarzia, Vincenzo; D’Onofrio, Augusto; Lorenzoni, Giulia; Chiminazzo, Valentina; Gregori, Dario; Gerosa, Gino (Interactive cardiovascular and thoracic surgery, 2021)
The aim of this study was to evaluate short- and long-term clinical outcomes, including the perceived health-related quality of life, in patients younger than 65 years having undergone aortic valve replacement either with biological or mechanical valve prostheses. Between 2002 and 2013, 242 consecutive patients <65 years of age underwent isolated aortic valve replacement at our institution, either with biological (n = 134, 55.4%) or mechanical (n = 108, 44.6%) prostheses. Survival, health-related quality of life, short- and long-term clinical outcomes and echocardiographic data were analysed with a retrospective, single-centre study. Propensity matching was performed. No significant difference in survival was found between the 2 groups (mechanical versus biological: 100% vs 96.6% at 1 year, 98.2% vs 93.1% at 5 years and 92.3% vs 83.4% at 10 years after surgery, P = 0.091). For all the interviewed patients (n = 161, 66.5%), perceived quality of life at the latest follow-up was excellent. Need for reoperation was higher in the bioprosthetic group (8% vs 0%, P = 0.995), whereas the rate of major bleedings was higher in the mechanical valve group (3% vs 20%, P = 0.094). The mean and maximum transvalvular pressure gradients were 20.5 ± 9.7 and 37.4 ± 17.5 mmHg in the biological group and 14.8 ± 4.8 and 26.6 ± 9.2 mmHg in the mechanical group (P = 0.014). No significant differences were found between biological and mechanical valves in terms of patients' survival, clinical outcomes and quality of life. Mean and maximum transvalvular pressure gradients were significantly higher in the biological group. The majority of patients would opt for the same prosthesis type, if asked to choose again.